Kewenangan Notaris terhadap Pembuatan Covernote - I Made Ari Nurjaya; I Nyoman Sumardhika; Ida Ayu Putu Widiati (Jurnal Konstruksi Hukum, 2020)
One of the legal products made by notary as a part of their authorities is a deed, both authentic deeds and underhand-made deeds. In addition to these deeds, a notary also has the authority to issue a certificate which is commonly referred to as a covernote. A certificate or covernote is a statement or note in the form of information confirming that a land ownership deed is in the process of a certificate making that is due to a process of roya, transfer of name of land ownership and splitting of one certificate into two. This study examines two issues related to notary authority, namely the basis for the notary’s authority in issuing a covernote and the legal consequences of making the covernote. This study uses a normative legal research method and a conceptual approach as well as a statutory approach. The results showed that the covernote issued by a notary was actually an ordinary certificate, not a legal product of a notary. Covernote only contains an explanation of the deed that is in the process of certification which has not been completed and will be completed within a period determined by the notary itself, so the covernote is not legally binding. The notary is authorized to make a covernote, but it is not regulated in the laws and regulations so that, if it is concluded, the covernote is not a legal product of a notary. The legal consequences for the notary if they fail to carry out the covernote, they can be held liable to solve them immediately. The legal consequence of not fulfilling the contents of the covernote is a violation of Article 1366 of the Criminal Code because notaries are considered negligent in carrying out their duties and authorities.